Public trust in the European legal systems: independence, accountability and awareness - Garoupa, Nuno (2020)
Two findings stand out in the literature on public attitudes vis- a-vis courts. The first is that judicial independence increases public trust. The second is that ‘to know courts is to love them’. In this study, these stylised facts are used as a starting point to ask three questions. First, is there also a role for judicial accountability in fostering public trust, above and beyond that played by independence? Second, could it be that only the most aware citizens are sensitive to such properties of the judicial system? Third, is the notion that ‘to know courts is to love them’ limited to systems with high levels of judicial independence and accountability? Using recently available macro-level indicators of judicial independence and accountability and the high-quality survey data collected by the European Social Survey in 32 countries throughout more than a decade, this study provides evidence that the answers to these questions are positive.